Influence of MHD for Newtonian Fluid and Heat Transfer in Microchannals between Two Parallel Plates Using HAM - Ahmed, Marwan (Iraqi Journal of Science, 2023)
The aim of this paper is the study of the influence magnetic field on steady stateflows and heat transfer in microchannels between two parallel plates.It is found that the motion equations are controlled by many dimensionlessparameter, namely magnetic field parameter M Reynolds number Re, physicalquantity at wall W and Knudsen number Kn also found that the energy equationsare controlled by many dimensionless parameter, namely magnetic field parameterM Reynolds number Re, physical quantity at wall W and Knudsen number Kn ,Prinkman number Br and Peclet number Pe.The equations which controlled this type of fluid flow are complicated, so findingan analytical solution is not easy.We obtained the velocity and energy distribution by using homotopy analysismethod (HAM).We have been studied the influence of all the physical parameters, that mentionedabove on the velocity And heat transfer distribution .This study is done through drawing about (30) graph by using the Mathematicapackage.